Предмет: Математика, автор: Alxvn

Реши уравнение: 5(3x - 7) - 3(8x - 11) = 3(8x + 7) . Ответ:

Ответы

Автор ответа: andrdys
26

Ответ:

5(3х-7) - 3(8х-11) = 3(8х+7)

15х - 35 - 24х + 33 = 24х + 21

15х - 24х -24х  = 21 + 35 - 33

-33х =23

х = 23/(-33)

Ответ: -\frac{23}{33}

Пошаговое объяснение:


shaldykbejbarys: Спасибо все правильно!
Mutuzik: Верно
Автор ответа: iramazurk
2

Ответ:

Пошаговое объяснение:

5(3х - 7) - 3(8х - 11) = 3(8х + 7)

15х - 35 - 24х + 33 = 24х + 21

15х - 24х - 24х = 21 + 35 - 33

-33х = 23

х = 23 : (-33)

х = -23/33


vahitovaamina509: ответ: - 23/33
Похожие вопросы
Предмет: Математика, автор: 123456789042852